Socio-oceanography: an opportunity to integrate marine social and natural sciences - Popova, Ekaterina; Aksenov, Yevgeny; Amoudry, Laurent O.; Becker, Amani; Bricheno, Lucy; Brown, Jennifer M.; Clare, Michael A.; Evans, Alan; Evans, Claire; Fowell, Sara E.; Jevrejeva, Svetlana; Jacobs, Zoe; et al. (Frontiers in Marine Science, 2023)
Marine natural sciences have been instrumental in helping society understand how ocean systems operate and the threats they face. However, there is a growing realisation that the societal challenges related to the marine environment can only be addressed through more effective integration with all aspects of social sciences. Nevertheless, to date, social sciences remain insufficiently integrated into marine research. Recognising historical weaknesses and drawing on the authors’ own experience of interdisciplinary research, albeit writing primarily from a natural marine science perspective, we propose a series of steps to promote integrated marine research inclusive of strong social science. We suggest that changing the perspectives and attitudes of natural scientists is key. The inherent interconnectivity between the ocean and society ensures that nearly everything we do in the marine natural sciences has the potential to influence and, perhaps address, ongoing and future societal challenges. Consequently, a key challenge for natural scientists is to recognise and communicate this in an accessible manner outside their own disciplines. To attempt to address these issues, we introduce the concept of “Socio-oceanography” which we define as an area of research that takes a “whole system” approach to the marine environment. It focuses on the challenges which require advancement of both natural and social science components, especially on those where the feedbacks between social and natural components are beginning to emerge. Here, we discuss its scope, challenges to its effective application and key steps to catalyse interdisciplinary approaches using this concept.